Factors Related to Husband's Involment in Antenatal Care Visits in High Risk Pregnant Women - Nurhalimah Juneldi; Vaulline Basyir; Rosfita Rasyid; Syamel Muhammad; Rozi Sastra Purna; Hasmiwati (PT FORMOSA CENDEKIA GLOBAL, 2024)
High-risk pregnancy is a pregnancy that can cause harm and complications to the mother and fetus during pregnancy, childbirth or after delivery compared to normal pregnancy and childbirth. The aim of this research is to determine